THE RELATIONSHIP BETWEEN LANGUAGE AND COGNITION - Yodgorova Diyora Jo‘rabek qizi (Modern American Journals, 2025)
This scientific article provides a comprehensive analysis of the interrelation between language and cognition from linguistic, psychological, and cultural perspectives. The main objective of the study is to determine the role of language in shaping human cognition, the mechanisms through which cognition is expressed via language, and how these processes are manifested in cultural contexts. The article examines theoretical foundations such as the Sapir–Whorf hypothesis, Chomsky’s theory, and Vygotsky’s model, alongside the views of Uzbek thinkers including Alisher Navoi, Abdulla Avloniy, Cho‘lpon, as well as modern Uzbek scholars. The analytical section discusses linguistic relativism, cognitive linguistics, and psycholinguistics to explore the formation of cognitive structures, decision-making processes, and cultural differences across languages. The findings reveal the complex, bidirectional relationship between language and cognition, offering theoretical and practical foundations for further research in Uzbek linguistics.
Keywords: Cognitive linguistics, Linguistic relativism, Universal grammar, Psycholinguistics, Cultural cognition, Language model, Cognitive structures, Worldview through language, Alisher Navoi, Abdulla Avloniy, Cho‘lpon, Uzbek linguistics, Language and consciousness, Language and thinking.